Vectors, host range, and spatial distribution of Dirofilaria immitis and D. repens in Europe: a systematic review - Carolin Hattendorf; Renke Lühken (Infectious Diseases of Poverty)
Abstract Background Dirofilaria immitis and D. repens are mosquito-borne nematodes with dogs as primary hosts, but other mammalian species including humans can be also infected. In the last century, circulation of both pathogens was predominantly restricted to Southern Europe. However, different studies indicated a potential establishment in Central, Eastern and Western parts of Europe as an increasing threat to animal and human health. Therefore, we conducted a systematic literature review of Dirofilaria data in Europe to give a comprehensive overview of potential mosquito vectors and vertebrate hosts, including the collection of different metadata (e.g. sampling year and site), allowing to analyse the spread pattern of the parasites in Europe. Methods On 24 January 2022, we conducted a systematic literature review of all available publications in the PubMed database reporting D. immitis and D. repens screening in mosquitoes and mammalian vertebrates in Europe. We only included acute infection of Dirofilaria spp., i.e. excluding studies only screening antibodies, and in addition noted the travel history and the accuracy of the sampling locations. These data were used to analyse the range of potential vectors and hosts and for a comparison of the spatial distribution between the twentieth and twenty-first century. Results Both nematodes appear to have a high overlap of Aedes, Anopheles and Culex as potential vector species, which are abundant in Europe. Most published D. immitis infections were reported in dogs, while D. repens predominantly were reported in humans. Dirofilaria immitis infections were detected in a wider range of wild and zoo animals. Compared to the last century, many more countries especially in Central Europe were affected by Dirofilaria spp. circulation, illustrating a significant spread over the last 20 years. Conclusions Our findings suggest that D. immitis and D. repens are a growing health concern for animals and humans in Europe. Continuous globalisation and climate warming will probably lead to a further spread and increased circulation in the future. All data are made available open access, which will enable further analysis. Graphical Abstract